The current feeding practices, fecal pH and volatile fatty acid concentration in horses in Kuala Lumpur Selangor and Putrajaya - Nurul Sirin Zailani (2017)
Most of simple carbohydrates in horse diets are digested in the small intestine. Some of simple and complex cerbohydrates and excess starch in horse diets are digested by microorganisms in the hindgut and the end products are volatile fatty acids (VFA) which mainly comprised of acetate, propionate and butyrate. Volatile fatty acids may supplies 25% or more of the energy needed by the horse. Acetate tends to be used for energy or for fatty acid synthesis meanwhile propionate can be used for energy or the maintenance of blood glucose levels. Volatile fatty acid concentration varies when horse are feed with different forage-concentrate ratio. In Malaysia, particularly in Kuala Lumpur, Selangor and Putrajaya, feeding practice error in term of forage-concentrate ratio occur within the equin industry which may lead to horses suffering from digestive problems. A study was conducted to investigate the feeding practices, fecal pH and fecal volatile fatty acid concentration of horses. Thirty-eight light bred horses consisted of 31 geldings and 7 mares were chosen. Their ages were between 4 and 22 years. The work type of the horses ranged from moderate to very heavy. Lists of horse information on the age, gender, breeds, weight, workload and feeding practices of the stables were obtained from each stable through a survey. The forage-concentrate ratio was culculated. Fecal samples were collected from the selected horses for analysis of pH and volatile fatty acid concentration. The fecal pH was measured using pH meter and volatile fatty acid concentration was measured using gas chromatography. All stables did not meet the suggested forage-concentrate ratio according to the workload of horses as the horses were fed higher forage ratio than the ideal ratio and lower concentrate than the ideal ratio. This causing the fecal acetate, propionate and butyrate ratios were higher than the normal ratio of 70:20:10 to 75:15:5. Despite of that, the average fecal pH in all the horses fell within the optimum pH of 6.85.